Interhemispheric microstructural connectivity in bitemporal lobe epilepsy with hippocampal sclerosis. (June 2015) - Miró, Júlia; Gurtubay-Antolin, Ane; Ripollés, Pablo; Sierpowska, Joanna; Juncadella, Montse; Fuentemilla, Lluís; Sánchez, Verónica; Falip, Mercè; Rodríguez- Fornells, Antoni
Abstract: Temporal lobe epilepsy (TLE) is the most common form of focal epilepsy. The most frequent pathologic finding in this condition is hippocampal sclerosis (HS). In addition, in a small proportion (14–23%) of refractory TLE patients, the presence of HS is bilateral. TLE involves grey matter (GM) and white matter (WM) abnormalities in a wide cortico-subcortical network. However, the impact of neuronal loss on specific WM fiber pathways and associated functional systems as well as seizure propagation pathways remains unclear. There is still much controversy regarding the role of the commissures (corpus callosum, hippocampal commissure and anterior commissure) in interhemispheric seizure propagation. This study aimed to investigate the integrity of WM interhemispheric connectivity in a singular sample of patients with TLE and bilateral HS using structural magnetic resonance imaging (MRI). We performed multimodal structural MRI [high resolution T1-weighted and diffusion tensor imaging (DTI)] analyses of seven patients with medically refractory TLE with bilateral HS, fourteen unilateral left TLE patients and fifteen matched healthy individuals. Whole-brain voxel-wise analysis techniques were used. These patients evidenced WM derangement [reduced fractional anisotropy (FA), increased mean diffusivity (MD) or reduced WM volume] in temporal and extratemporal tracks, but also in commissural pathways, compared to the unilateral left TLE patients and the control group. Presence of reduced FA or increased MD in the fornix, cingulum and uncinate fasciculus in addition to reduced WM volume in the fornix was also encountered. Neuropsychological assessment was performed without significant correlations with structural data. The current results support the idea that commissural pathways play a contributory role in interhemispheric TLE seizure propagation in bilateral HS and offer new perspectives about the long-term effects on interhemispheric connectivity associated with seizure propagation patterns in TLE patients.